EFFECTS OF TEAM NURSING METHOD TRAINING ON NURSES’ PERFORMANCE - Agus Saputra; Blacius Dedi; Sudibyo Soepardi (Nursing Current: Jurnal Keperawatan, 2021)
Team nursing is a method of care delivery that employs a group of individuals led by a knowledgeable nurse to provide nursing care to a cluster of patients. This study aims to analyse nurses’ performance after undergoing training on the team nursing method in a hospital setting. The quasi-experimental pre and post-test design was used. Purposive sampling was utilized in selecting 38 nurses who agreed to participate in the study; 19 were assigned to the intervention group and another 19 to the control group. The nurses in the intervention group joined a training in team nursing as a care delivery method and were observed and supervised for six weeks. A questionnaire was used to measure nurses’ performance in providing care. Results were analysed using rate, mean, Chi Square test and Multivariate Logistic Regression Analysis. The findings revealed that most of the respondents were between 20-30 years old with more than five years of work experience. The nurses in the intervention group significantly improved their performance by 11.35% after the team nursing method training (p value 0.0001). The OR of 27.7 may suggest that the training greatly influenced improvement in their performance. Furthermore, the training may have improved nurses' work performance 21.7 times compared to those who did not join it. The researchers recommend that training on team nursing method as a care delivery system be implemented in all units of the hospital to help improve the provision of nursing care.